Unraveling the association between vaccine attitude, vaccine conspiracies and self-reported side effects following COVID-19 vaccination among nurses and physicians in Jordan - Malik Sallam; Hiba Abbasi; Rawan J. Obeidat; Reham Badayneh; Farah Alkhashman; Aseel Obeidat; Dana Oudeh; Zena Uqba; Azmi Mahafzah (Vaccine: X, 2023)
Background: The negative impact of vaccine conspiracies is linked with negative health behavior. The aim of the current study was to examine the association between attitudes toward booster COVID-19, influenza, and monkeypox (mpox) vaccinations with post-COVID-19 vaccine side effects, vaccine conspiracies, and attitude towards mandatory vaccination among nurses and physicians in Jordan. Methods: A structured closed-ended questionnaire was used to collect data on demographics, COVID-19 history, COVID-19 vaccine type and doses received, self-reported side effects post-COVID-19 vaccination, acceptance of booster COVID-19, seasonal influenza, and mpox vaccinations, attitudes towards mandatory vaccination, and beliefs in vaccine conspiracies. Results: The study sample comprised a total of 341 participants. Acceptance of yearly booster COVID-19 vaccination was expressed by 46.6% of the sample, while 73.3% accepted seasonal influenza vaccination, and only 37.0% accepted mpox vaccination. A higher frequency of self-reported side effects following the first COVID-19 vaccine dose was associated with embrace of vaccine conspiracies and vaccine type. For the second vaccine dose, a higher frequency of self-reported side effects was associated with the embrace of vaccine conspiracies, older age, and affiliation to private sector. In multinomial logistic regression analyses, the lower embrace of vaccine conspiracies was associated with lower odds of reporting side effects post-COVID-19 vaccination. The lower embrace of vaccine conspiracies and favorable attitude towards mandatory vaccination were associated with the willingness to get COVID-19, influenza, and mpox vaccinations. Conclusion: The study findings highlighted the negative impact of embracing vaccine conspiracies on health-seeking behavior among nurses and physicians. The findings indicated that the willingness to get vaccinated was associated with lower endorsement of vaccine conspiracies. Additionally, the lower embrace of vaccine conspiracies was associated with a lower frequency of self-reported side effects following COVID-19 vaccination. These results emphasize the importance of addressing vaccine misinformation and promoting accurate information to ensure optimal vaccine uptake and public health outcomes.